Risk stratifying gastric ulcers: development and validation of a scoring system. Issue 2 (26th February 2021) - Brindle, William M; Grant, Rebecca K; Smith, Marianne; Suddaby, Meghan; Wallace, Angus; Gillespie, Sarah-Louise; Church, Nicholas I; Noble, Colin L; Penman, Ian D; Plevris, John N; Robertson, Alexander R; Watson, Eleanor F; et al.
Abstract : Objective: Debate is ongoing regarding the need for universal endoscopic follow-up to ensure gastric ulcer healing. We aimed to assess the value of follow-up oesophago-gastro-duodenoscopies (OGDs) for gastric ulcer healing and stratify patients according to risk of malignancy by developing a risk score. Design/method: All patients in National Health Service (NHS) Lothian with an index OGD and a diagnosis of gastric ulcer between 1 January 2014 and 31 December 2018 were identified. Data were analysed with logistic regression to identify factors significantly associated with a diagnosis of cancer; a risk score was derived and externally validated. Results: 778 patients were identified and 60.3% (469/778) of patients had a follow-up OGD. 8.6% (66/778) of patients were diagnosed with cancer. No cases of cancer were found on follow-up OGD of a benign appearing ulcer with negative biopsies. Macroscopic suspicion of malignancy was present at index OGD in 100% (3/3) of those diagnosed with cancer on subsequent OGDs. Older age (p=0.014), increased ulcer size (p<0.001) and non-antral location (p=0.030) were significantly associated with malignancy. A risk score (area under the curve (AUC) 0.868, p<0.001, minimum score=0, maximum score=6) was derived from these variables. 78.0% of patients with malignant ulcers scored ≥3, only 15.8% with benign ulcers scored ≥3 (negative predictive value (NPV) 97.4%). External validation yielded an AUC of 0.862 (p<0.001) and NPV of 98.6%; 84.0% of those with malignant ulcers scored ≥3. Conclusion: Ulcers with a combination of macroscopically benign appearances, at least six negative biopsies and a low risk score do not necessarily need endoscopic follow-up.